Herd behavior in the choice of motorcycles: Evidence from Nepal - Nilkanth Kumar; Nirmal Kumar Raut; Suchita Srinivasan (ETH Zurich, CER-ETH - Center of Economic Research, 2022)
This article sheds light on a scarcely explored area of research related to herd behavior in urban settings of developing economies, where the use of motorized twowheelers has been increasing rapidly. Using primary survey-based data from Nepal, we examine whether potential motorcycle buyers in the Kathmandu valley exhibit herd behavior or price-conscious behavior when making a hypothetical choice decision and then evaluate the determinants of the observed behavior. Using factor analysis, the paper identifies distinct homogeneous groups of respondents based on their preferences towards motorcycle attributes and on their psychological traits and attitudes. Not only do we find a prevalence of herding in the choice of motorcycles, the results also find strong suggestive evidence that, in addition to gender and income, several latent factors related to preferences and psychological traits might play a crucial role in determining the herd behavior. We discuss policy implications in the context of consumer behavior and environmental policy in the backdrop of rapid vehicle demand and dangerous air pollution levels.
Keywords: D12; D83; D91; Q58; 330; herd behavior; determinants; motorcycle choice; psychological factors; bounded rationality; Nepal